Coconut Cultivation in Northeast India - Hebbar, K B; Bhat, Ravi; Thamban, C; Subramanian, P; Das, Alpana (Indian Horticulture, 2024)
Coconut cultivation has been spreading to non-traditional areas as well including different states in the Northeast region of the country since the last many years. Assam, Tripura and Nagaland are the major Northeastern states having coconut cultivation, together covering about 26,480 ha (as per 2020-21 statistics) and a total annual production of 175.88 million nuts. The average productivity of coconut in these three states is only 6,642 nuts per ha which is much less than the national average of 9,430 nuts per ha. Other Northeastern states viz., Arunachal Pradesh, Manipur, Meghalaya and Mizoram are also having small extent of coconutcultivation. There is ample scope for enhancing the area under coconut cultivation in the Northeastern states having congenial agro-ecological situations pertaining to climate and soil. Besides, the productivity and income from the existing coconut holdings can also be considerably increased through better integration of technologies, especially improved varieties, integrated nutrient management,cropping/farming systems and integrated pest and disease management.